Perceived Stress Due COVID-19 Pandemic Among Employed Professional Teachers - Oducado, Ryan Michael; Rabacal, Judith; Moralista, Rome; Tamdang, Khen (IJERI: International Journal of Educational Research and Innovation, 2020)
The unexpected occurrence of the COVID-19 outbreak has undeniably disrupted the normalcy of life. Stress has become an important concern in education since the COVID-19 outbreak. This descriptive-correlational online survey administered in August 2020 utilized the COVID-19 Perceived Stress Scale (COVID-19 PSS-10) to assess the COVID-19 perceived stress among employed Filipino teachers. Whitney U and Kruskal–Wallis tested for differences while Spearman’s rho was used to analyze correlation between variables. Results demonstrated that more than half of teachers experienced moderate COVID-19 stress. Females experienced significantly higher COVID-19 stress compared to males. A negative correlation was noted between self-rated health and COVID-19 stress while a positive correlation was found between perceive risk of getting COVID-19 infection and COVID-19 stress. This study highlights that steps must be undertaken to help teachers deal with the stress of the COVID-19 crisis as well as they must be provided or taught with stress management interventions during this pandemic. This study could be used as a baseline for future research to assess the impact of COVID-19 stress among professional teachers.